O processo de implementação de reformas gerenciais na educação básica: São Paulo (2007-2010) e Minas Gerais (2004-2010) em perspectiva comparada - Prado, Mauricio Almeida (2012)
The study of the implementation process was considered the missing link in the public policy theory. The awakening of interest in the topic comes from the early 1970s after a series of failures of public programs to combat poverty in the United States of America. The small number of studies in public education management in Brazil can also be observed. Most of Brazilian authors have been limited their analysis to one or two innovations and their impact on improving the quality of education. The recent educational reforms, however, include various innovative components that have been implemented jointly. This thesis conducts an investigation into the process of implementing managerial reforms of education in two important Brazilian states: Minas Gerais and São Paulo. The focus of the study is the implementation process or, in other words, the action of multiple agents of executive power in order to operationalize each component of the reform. This study concludes that effective implementation is directly linked to the nature of the component in question and the managerial style of implementation that it requires. The components whose implementation depends exclusively on the senior managers are directly linked to the political force of the government and the quality of theses central members of the reform. As for those components whose effective implementation requires the direct action of teachers, governments should act in the structuring of middle management so that it effectively exercise the functions of mediation, support and monitoring of teachers in loco.